THE DISCOURSE OF BANNER MESSAGES AT STUDENT PROTESTS IN SERBIA (2024–2025) - Perišić, Nikola (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2026)
Student protests in Serbia have been ongoing since December 2024 and grew out of public gatherings in November 2024 calling for political responsibility after the collapse of the canopy at the Novi Sad railway station, which killed sixteen people. In response, students held a daily memorial at 11:52am (the exact time the canopy fell on November 1, 2024), lasting sixteen minutes, that is, one minute of silence for each victim. In late November, several participants in these memorials were hit by cars in multiple locations in Belgrade, and in some cases the drivers who endangered them were found to be connected to Serbia’s ruling parties. All of this contributed to students’ decisions, from December 2024 onward, to suspend classes and block university facilities, while, at pre-defined time periods, organizing mass protests in various Serbian cities throughout 2025. At those protests a wide array of banners were displayed to focus public attention on the messages students wanted to send. The prevailing banner messages aligned with the values promoted during the protests: freedom, responsibility, anti-corruption, etc. The dominant discourse relied on allusive and ironic elements, often inspired by public statements by government officials, by popular culture elements (song lyrics, and film or TV lines), and by the “re-branding” of slogans from the 1990s protests, with the intent to evoke parallels and to link Aleksandar Vučić’s rule to that of Slobodan Milošević.